Employee Performance View of Human Relations and Rewards - Marlinda (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
This research aims to analyze influence the performance of JNE employees is seen from human relations and rewards in Pekanbaru. The research was conducted by means of descriptive analysis method and the sample used was all employees of JNE Pekanbaru, totaling 60 respondents using the census method or saturated sample. The analysis technique used by researchers is multiple linear regression analysis carried out with technology, namely using SPSS, 20. The results of the study state that the human relation variable partially has a positive and significant influence on the performance of JNE Pekanbaru employees, namely the t-count is greater than the t-table, while the reward partially also has a positive and significant effect on the performance results of JNE Pekanbaru employees t- calculate the size of the t-Table. Then after testing simultaneously it was found that human relations and rewards have a positive and significant effect on the performance of JNE Pekanbaru employees, namely 53.4% and 46.6% influenced by other variables not examined.